1993
DOI: 10.1159/000243974
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intrauterine Growth on Intestinal Length in the Human Fetus

Abstract: Standards for human fetal intestinal length are not well established but have important implications for the care of the preterm and intrauterine growth-retarded (IUGR) infant. Our purpose was to examine the relationship between intrauterine growth and intestinal length in the human fetus. One hundred infants were studied. Birth weight and gestational age ranged from 76 to 4,385 g and from 12 to 42 weeks, respectively. Twenty-one infants were noted to be IUGR. Intestinal length (total, small, large) increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 7 publications
2
40
0
Order By: Relevance
“…Previous studies also observed changes in the size and histopathology of the thymus in animal models of IUGR and stillborn infants (Lansdown 1977;D'Inca et al 2010c). Our findings agree with previous observations that also suggested that IUGR was associated with poorly developed SIs, which were shorter and thinner than those of normal piglets, although the relative length of the SI in IUGR was longer (Wang et al 2005;D'Inca et al 2010c;Shanklin and Cooke 1993). Michiels et al (2013) also reported maldevelopment of the digestive tract of the IUGR piglets in the post-weaning period.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies also observed changes in the size and histopathology of the thymus in animal models of IUGR and stillborn infants (Lansdown 1977;D'Inca et al 2010c). Our findings agree with previous observations that also suggested that IUGR was associated with poorly developed SIs, which were shorter and thinner than those of normal piglets, although the relative length of the SI in IUGR was longer (Wang et al 2005;D'Inca et al 2010c;Shanklin and Cooke 1993). Michiels et al (2013) also reported maldevelopment of the digestive tract of the IUGR piglets in the post-weaning period.…”
Section: Discussionsupporting
confidence: 90%
“…This phenomenon could explain the reduction in intestinal development observed at birth in infants with IUGR (20) and some animal models of IUGR (21). IUGR impairs cell proliferation (22) and absorptive (23) and digestive (24) functions in small intestine.…”
mentioning
confidence: 93%
“…IUGR impairs cell proliferation (22) and absorptive (23) and digestive (24) functions in small intestine. It was found to produce alterations in colonic development, such as a reduction in colonic length or weight, or in the number of goblet cells in animal models of IUGR (20,25). Yet, the specific effect of IUGR on mucin gene expression and secretion has not been addressed.…”
mentioning
confidence: 99%
“…ntestinal epithelial development changes immediately after birth, with an age-dependent enterocyte proliferation and differentiation pattern (1). Intestinal cell growth peaks at birth (2,3) upon the stimulation exerted by growth factors in amniotic fluid and in human milk (4,5), but also as a consequence of dietary changes (6).…”
mentioning
confidence: 99%